2021
DOI: 10.2967/jnumed.120.258467
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-DOTA-FAPI-04 PET/MR in the Evaluation of Gastric Carcinomas: Comparison with 18F-FDG PET/CT

Abstract: We sought to evaluate the performance of 68 Ga-DOTA-FAPI-04 ( 68 Ga-FAPI) PET/MR for the diagnosis of primary tumor and metastatic lesions in patients with gastric carcinomas and to compare the results with those of 18 F-FDG PET/CT. Methods: Twenty patients with histologically proven gastric carcinomas were recruited, and each patient underwent both 18 F-FDG PET/CT and 68 Ga-FAPI PET/MR. A visual scoring system was established to compare the detectability of primary tumors and metastases in different organs/re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
114
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(127 citation statements)
references
References 22 publications
13
114
0
Order By: Relevance
“…Recently, 68Ga-FAPI has been clinically adopted, allowing researchers to obtain a variety of tumor images with very high uptake and image contrast, paving the way for new applications in tumor characterization, staging, and treatment. Qin et al (99) evaluated the performance of 68Ga-DOTA-FAPI-04 (68Ga-FAPI) PET/MR in the diagnosis of primary tumors and metastatic lesions in patients with gastric cancer and compared it with 18F-FDG PET/CT. The results show that, due to the high expression of FAP in gastric cancer and its metastatic tissues, 68Ga-FAPI PET/MR is significantly superior to 18F-FDG PET/CT for the diagnosis of primary gastric cancer and its metastatic lesions.…”
Section: Inhibitor Of Fapmentioning
confidence: 99%
“…Recently, 68Ga-FAPI has been clinically adopted, allowing researchers to obtain a variety of tumor images with very high uptake and image contrast, paving the way for new applications in tumor characterization, staging, and treatment. Qin et al (99) evaluated the performance of 68Ga-DOTA-FAPI-04 (68Ga-FAPI) PET/MR in the diagnosis of primary tumors and metastatic lesions in patients with gastric cancer and compared it with 18F-FDG PET/CT. The results show that, due to the high expression of FAP in gastric cancer and its metastatic tissues, 68Ga-FAPI PET/MR is significantly superior to 18F-FDG PET/CT for the diagnosis of primary gastric cancer and its metastatic lesions.…”
Section: Inhibitor Of Fapmentioning
confidence: 99%
“…Overexpression of FAPs in gastric carcinomas has also been demonstrated (41)(42)(43). Quin et al investigated 20 gastric cancer patients and described the superiority of 68 Ga-FAPI04 PET/MR over 18 F-FDG PET/CT in visualizing the primary tumors and most metastatic lesions (44). Pang et al ( 45) evaluated 68 Ga-FAPI04 PET/CT of 20 patients with gastric carcinoma and reported higher detection rates and mean SUV max than 18FDG PET/CT.…”
Section: Fibroblast Activation Protein-targeted Imaging In Oncologymentioning
confidence: 99%
“…Linz et al (38) Oral cavity squamous cell carcinoma 10 Compared with 18 F-FDG and cervical MRI, 68 Ga-FAPI can reduce patient morbidity, minimizing the number of neck dissections due to false-positive cervical lymph nodes. Qin et al (44) Gastric carcinomas 20 68 Ga-FAPI PET/MR showed better diagnostic performance than 18 F-FDG PET/CT in visualizing the primary and metastatic lesions of gastric cancer. Pang et al (45) Gastric, duodenal, and colorectal cancers 35 68 Ga-FAPI PET/CT showed superior diagnostic performance.…”
Section: Syed Et Al (36)mentioning
confidence: 99%
See 1 more Smart Citation
“…68 Ga-FAPI is a novel tumor-targeting agent, as fibroblast activation protein is overexpressed in cancer-associated fibroblasts (1)(2)(3). Existing research has shown that FAPI revealed favorable pharmacokinetics and biodistribution in vivo and a clear delineation of primary tumors and their metastases (4)(5)(6)(7). With the increasing use of 68 Ga-FAPI in clinical trials, accurate interpretation of unexpected findings remains a challenge, because the impact of accidental findings on patient management may be significant.…”
Section: Introductionmentioning
confidence: 99%